Lauromacromia bedei sp. nov. from the State of Minas Gerais, Brazil (Odonata, Corduliidae) - Machado,Angelo B. M. (2005)
Lauromacromia bedei is described and illustrated from a single male specimen collected in a river at the "cerrado" region of the State of Minas Gerais, Brazil.